Are Participants in a Street-Based HIV Testing Program Able to Perform Their Own Rapid Test and Interpret the Results? - de la Fuente, Luis; Rosales-Statkus, María Elena; Hoyos, Juan; Pulido, José; Santos, Sara; Bravo, María José; Barrio, Gregorio; Fernández-Balbuena, Sonia; Belza, María José; the Madrid Rapid HIV Testing Group (PLOS ONE, 2012)
Objective Availability of over-the-counter rapid HIV tests could improve access to testing those reluctant or unable to use current services. We aimed to evaluate the feasibility of HIV self-testing using a finger-stick whole-blood rapid test (Determine™ HIV Combo) to detect both antigen and antibody. Methods Before being tested, 313 participants in a street-based testing program were given adapted instructions and a test kit, and performed the self-test without supervision. These participants, together with another 207 who performed supervised self-testing, received additional instructions on how to interpret the test results shown in six colour photos and filled out a questionnaire. Logistic regression and generalized estimating equations (GEE) were used in the statistical analysis. Results About 8.0% (95%CI:4.8%–11.2%) obtained an invalid self-test. An invalid result was inversely associated with male participants who had sex with men (OR = 0.3;95%CI:0.1–1.0). Of the 3111 photos interpreted,4.9% (95%CI:4.1–5.7) were incorrect. Only 1.1% (95%CI:0.3–1.8) of the positive results were interpreted as negative. Age 30 or older (OR = 2.1; 95%CI:1.2–3.7), having been born in Latin America (OR = 1.6; 95%CI:1.1–2.2),and not having university education (OR = 2.1;95%CI:1.2–3.7) were associated with misinterpreting test results in the GEE. Participant's perceptions of both their proficiency when conducting the test and interpretation were related with actual outcomes. Most participants (83.9%) were more motivated than before to use the self-test in the future, and 51.7% would pay >10 Euros for the test if it was sold in pharmacies. Conclusions This is the first study showing that blood-based self-testing with current technology is feasible in HIV-negative participants demanding the test and without prior training or supervision. Bearing in mind that it was conducted under difficult weather conditions and using a complex kit, over-the-counter tests could be a feasible option to complement current diagnostic strategies. More studies are needed to accommodate technology, minimise interpretation mistakes and provide on-line support.